Investigation of Potential Bioactive Compounds And Assessment of Anti-diabetic Properties of Hydroclathrus Sp. Collected From The Bay of Bengal, Bangladesh - Akhter, Shomaya; Shohag, Sheikh; Alim, Md Abdul; Islam, Md Tohidul; Hossain, Mohammad Nazir (Bioresearch Communications, 2024)
Diabetes mellitus, a chronic metabolic disorder, has become a global health concern, prompting the exploration of alternative and sustainable sources for potential therapeutic agents. Seaweed extracts provide various benefits over synthetic medications, including lower toxicity and fewer side effects with diverse pharmacological properties, making them promising candidates for diabetes management. For this investigation, brown seaweeds, Hydroclathrus sp., were obtained from Saint Martin Island, Bangladesh. Following phytochemical analysis, the anti-diabetic efficacy of Hydroclathrus sp. was evaluated both in vitro and in vivo. In vitro studies showed that alpha-amylase inhibitory activity of 50% ethanolic extract of Hydroclathrus sp. was closely related to positive control acarbose. Besides, in vivo studies were conducted on alloxan-induced diabetes mice models, exploring the effects of Hydroclathrus sp. on blood glucose levels, and their biochemical profile was evaluated and found the algal extract at 100mg/kg body weight was more potent than the reference medicine (Glibinclamide) after 14 days of treatment. Lipid profiles and liver and kidney function tests also revealed the potent antidiabetic effects of 50% ethanolic extract of Hydroclathrus sp. These findings offer valuable information for the development of novel marine-derived anti-diabetic medications. However, further studies are required to elucidate and validate its true potential in diabetes. Bioresearch Commu. 11(1): 1698-1710, 2025 (January)